2016
DOI: 10.1111/jtxs.12190
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Food Difficulty Perception: Food Structure, Food Oral Processing and Individual's Physical Strength

Abstract: This study aims to study the effect of the interaction between food physics and human physical strengths on food oral processing and difficulty perception in the young population. As the first step in human nutrition is the food oral processing, special emphasis has been given to the oral strengths. Fracture mechanics of fifteen commonly consumed food products of fruits, vegetables and dairy origin were analysed using penetration test. Among the different products studied, six products (carrot, banana, mozzare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 51 publications
(103 reference statements)
6
26
0
Order By: Relevance
“…Laguna, Asensio Barrowclough, Chen, and Sarkar () studied the eating difficulty of six products (carrot, banana, mozzarella, potato, soft cheddar, and hard cheddar) and found that the hardest food, carrot required a greater number of chews and the longest processing time in mouth, which they found in accordance with the conclusion by Witt and Stokes (). However, hard cheddar was found the most difficult although it resided a shorter time in mouth and the break force was lower than carrot, which led these authors to think that it is not only the force at break but also the structural property of the food that plays an important role in perceived difficulty.…”
Section: Texture Studies Of Solid Foodssupporting
confidence: 61%
“…Laguna, Asensio Barrowclough, Chen, and Sarkar () studied the eating difficulty of six products (carrot, banana, mozzarella, potato, soft cheddar, and hard cheddar) and found that the hardest food, carrot required a greater number of chews and the longest processing time in mouth, which they found in accordance with the conclusion by Witt and Stokes (). However, hard cheddar was found the most difficult although it resided a shorter time in mouth and the break force was lower than carrot, which led these authors to think that it is not only the force at break but also the structural property of the food that plays an important role in perceived difficulty.…”
Section: Texture Studies Of Solid Foodssupporting
confidence: 61%
“…This is a non-invasive method which has ecological validity and is relatively simple to undertake. A pilot study was done in young population to check its validity and to identify any difficulty in the performance (Laguna, Asensio Barrowclough, Chen, & Sakar, 2016). Since dental status is likely to influence oral processing time and eating capability, the relationship between dentition, EC, oral processing and subjective measures was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Laguna et al. () also reported that the subjects could not open all of the packaging tested. The forces needed to open the packaging did not seem to be too high in relation to the subjects’ abilities as demonstrated through grip‐and‐pinch strengths.…”
Section: Guidelines For Designing Food Products For Scsmentioning
confidence: 99%
“…Laguna, Barrowclough, Chen, and Sarkar (), as part of the Optimizing Food for the Elderly Population Project (OPTIFEL) (http://www.optifel.eu), found that the most difficult closure type to open was the screw‐top (often vacuum‐packed) cap (Figure ). Other closures such as pull‐tab cans, tin‐can lids, easy‐to‐open packages, and opercula (Figure ) were cited as difficult to open by several populations (opercula is Latin and means “little lids”; it is the plural of operculum).…”
Section: Guidelines For Designing Food Products For Scsmentioning
confidence: 99%
See 1 more Smart Citation